Nutrition in the preterm infant: what's new?. Issue 3 (May 2016) - Cleminson, Jemma S.; Zalewski, Stefan P.; Embleton, Nicholas D.
Abstract : Purpose of review: The increasing recognition of the role of nutritional care for preterm infants continues to result in a proliferation of review articles, systematic reviews, observational studies and trials. In this article, we review a selection of important studies published in the last 12–18 months. Recent findings: The selected studies demonstrate the potential importance of light protecting parenteral nutrition solutions, the benefits of standardized concentrated parenteral nutrition solutions and the importance of insulin-like growth factor I in early life. Trials of immunonutrients (such as bile salt-stimulated lipase) and other bioactive peptides such as lactoferrin are in progress, and emerging data highlight the importance of vitamin D for immune regulation, and therefore its role in sepsis and gut function. Early oro-pharyngeal administration of colostrum appears to safely improve early immune development, and supports the increasingly common practice of immediate commencement of mothers' own breast milk. Despite this, studies continue to show that breastfeeding continuation rates could be improved. Data also highlight the potential role of macronutrient supply on other functional outcomes, such as retinopathy of prematurity. Finally, the importance of the unique nutritional needs of late and moderately preterm infants is starting to be recognized – a much larger group than the extremely preterm infants in whom many studies are focused. Summary: Earlier, more aggressive nutrient supply and feeding regimes, including optimal support of breastfeeding mothers to ensure adequate provision of own mother's milk, appear to improve growth and neurodevelopmental outcomes. The addition of bioactive proteins shows promise. Special focus needs to be reestablished for late and moderately preterm infants, who have particular nutritional and feeding support requirements. This review has highlighted the need for further research particularly in the areas of early parenteral nutrition, the optimal regime to improve early growth and neuronal effects, the optimal rate of growth and/or catch-up, and the role of immune nutrients.